2008
DOI: 10.5194/acp-8-5889-2008
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of pollutants from North China Plain to surface ozone at the Shangdianzi GAW Station

Abstract: Abstract.Regional ozone pollution has become one of the top environmental concerns in China, especially in those economically vibrant and densely populated regions, such as North China region including Beijing. To address this issue, surface ozone and ancillary data over the period [2004][2005][2006] from the Shangdianzi Regional Background Station in north China were analyzed. Due to the suitable location and valley topography of the site, transport of pollutants from the North China Plain was easily observed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
114
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(126 citation statements)
references
References 28 publications
10
114
2
Order By: Relevance
“…Diurnal variation patterns (particularly the peak times) are not the same in different areas. Our results agree well with the typical diurnal patterns for O 3 concentration at low-elevation locations (Kelly et al, 1984;Lin et al, 2008). However, it differed from the patterns from high-elevation sites.…”
Section: Calculation Of O 3 Concentration-based Indicessupporting
confidence: 87%
See 1 more Smart Citation
“…Diurnal variation patterns (particularly the peak times) are not the same in different areas. Our results agree well with the typical diurnal patterns for O 3 concentration at low-elevation locations (Kelly et al, 1984;Lin et al, 2008). However, it differed from the patterns from high-elevation sites.…”
Section: Calculation Of O 3 Concentration-based Indicessupporting
confidence: 87%
“…The mean O 3 concentration during the growing seasons was 31.3 ± 22.3 ppbV. The diurnal variation of O 3 concentration depends on the balance of many factors affecting O 3 formation (e.g., local photochemical reactions and horizontal or vertical transport) and destruction (e.g., deposition or chemical reactions) (Crutzen et al, 1999;Cape, 2008;Lin et al, 2008). In the early afternoon, in spite of the gradual decrease of radiation, the increasing temperature resulted in higher levels of chemical precursors, which then led to the rise in O 3 concentration.…”
Section: Calculation Of O 3 Concentration-based Indicesmentioning
confidence: 99%
“…This is evident from the diurnal cycle of NO (Figure 4a), which shows a pronounced morning peak. The NO concentration peaks between 7:00 and 8:00 (~17 ppb) and then gradually decreases to a low ambient level (~1 ppb) due to the titration of NO by O 3 , and also the rising boundary layer during the daytime [Lin et al, 2008.…”
Section: Time Series and Diurnal Variationsmentioning
confidence: 99%
“…The results showed that the factors significantly related to PM2.5 were SO 2, NO 2 and CO in spring; O 3 and CO in summer; SO 2, NO 2 and CO in autumn and SO2, NO 2, CO, O 3 in winter, respectively [5,6] . (2) The concentration of PM10 was highly affected by season and climate, for example, PM10 was significantly influenced by coal in heating period, but by sandstorm weather in non-heating period. The concentration of PM2.5, SO 2 and NO 2 all increased in heating period, while SO 2 was the most sensitive pollutant.…”
Section: Resultsmentioning
confidence: 88%